The use of digital badges by undergraduate nursing students: A three-year study. (September 2018) - Garnett, Timna; Button, Didy
Abstract: During a three-year study, 32% (n = 67) in 2015, 16% (n = 44) in 2016 and 55% (n = 161) of students in 2017 expressed an interest in using digital badges to enhance their learning. But who are these students? This paper explores the features of students who are interested in using digital badges as a motivational reward to prepare for weekly face-to-face classes through engaging with online activities and resources. This paper uses a first-year undergraduate Bachelor of Nursing bioscience topic at an Australian university to report nursing students' interests around playing games, their digital badge history during the topic, and their self-reported attitudinal interest in using digital badges to enhance and personalise their learning. Overall, the results indicate that some students chose to enhance their learning potential in class by earning digital badges prior to class. The results of this paper are relevant for nursing educators and educational designers seeking to integrate digital badges into motivational teaching practices, by evaluating the role digital badges play as a motivational game-based learning design element. Highlights: Students who are motivated to prepare for class by using digital badges may enhance their learning in class. Some high-achieving students are motivated to learn with digital badges. Over the course of the topic, the value of digital badges as a motivational tool decline with use, suggesting a potential novelty effect.